2018
DOI: 10.3171/2017.6.spine17130
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and technical factors associated with superior facet joint violation in lumbar fusion

Abstract: OBJECTIVEThe aim of this study was to evaluate the anatomical and surgical risk factors for screw-related facet joint violation at the superior level in lumbar fusion.METHODSThe authors conducted a retrospective review of a consecutive series of posterior lumbar instrumented fusions performed by a single surgeon. Inclusion criteria were primary lumbar fusion of 1 or 2 levels for degenerative disorders. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
1
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 24 publications
4
46
1
5
Order By: Relevance
“…Despite the identification of techniques that can bring more risks of violation, another point is to identify structures and parameters that can serve as a reference for location, and, theoretically, for the reduction of facet violation. 6,17,22 Among the factors pointed out as having a relation to the facet violation, Jia et al 23 showed that the lower the location, the higher the rate of facet violation, similar to the findings of Teles et al, 6 who reported 100% of facet violations at levels L4 and L5. These results are different from those indicated by our study, which identified the thoracic and L1 levels as more susceptible to facet violation.…”
Section: Anatomical Landmarks and Facet Violationsupporting
confidence: 54%
See 4 more Smart Citations
“…Despite the identification of techniques that can bring more risks of violation, another point is to identify structures and parameters that can serve as a reference for location, and, theoretically, for the reduction of facet violation. 6,17,22 Among the factors pointed out as having a relation to the facet violation, Jia et al 23 showed that the lower the location, the higher the rate of facet violation, similar to the findings of Teles et al, 6 who reported 100% of facet violations at levels L4 and L5. These results are different from those indicated by our study, which identified the thoracic and L1 levels as more susceptible to facet violation.…”
Section: Anatomical Landmarks and Facet Violationsupporting
confidence: 54%
“…4,5 Multiple techniques for lumbar supplementation/fixation have been proposed and used and, for reducing the risk of neurovascular injuries and for promoting great stabilization of the construction, pedicle screws have become the preferred method for posterior fixation in lumbar surgeries allowing the stability of the operated level. [6][7][8] Several techniques are proposed for the placement of pedicle screws, including the techniques of Magerl, 9 Roy-Camille et al, 10 and Weinstein et al, 11 among others. 12 In addition, with the popularization of minimally-invasive techniques for spine surgery, the quantity of pedicle screws placement by percutaneous technique is increasing.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations